2018
DOI: 10.3390/ijms19010250
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis and Identification of Possible Allergenic Proteins in Mature Pollen of Populus tomentosa

Abstract: Pollen grains from Populus tomentosa, a widely cultivated tree in northern area of China, are considered to be an important aeroallergen causing severe allergic diseases. To gain insight into their allergenic components, mature Populus tomentosa pollen proteins were analyzed by two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF/TOF MS). A total of 412 spots from mature pollen were resolved on pH 4–7 immobilized pH gradient (IPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…In this study, three spots (spots 58–60) were attributed to proteins with no clearly predicted, well-defined function. This is consistent with the findings of other pollen proteomic studies [14,46].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, three spots (spots 58–60) were attributed to proteins with no clearly predicted, well-defined function. This is consistent with the findings of other pollen proteomic studies [14,46].…”
Section: Discussionsupporting
confidence: 93%
“…Label-free quantification proteomics was applied in the study, as there is no required labeling reagents and limit to samples in experiments [32]. Compared to most proteomics research in Populus [16][17][18], more proteins were identified in our study (Figure 1a). It could be due to the main advantages of label-free quantification, which can achieve higher proteome coverage as compared to the most widely used 2-DE in Populus proteome [1,[16][17][18].…”
Section: Discussionmentioning
confidence: 92%
“…Label-free quantification proteomics was applied in the study, as there is no required labeling reagents and limit to samples in experiments [32]. Compared to most proteomics research in Populus [16][17][18], more proteins were identified in our…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomics analysis was used to characterize the allergens from P. tomentosa mature pollen. In total, 27 proteins were identified as putative allergens, such as heat shock protein, enolase, pollen Ole e 1 allergen, thioredoxin and profilins using the Structural Database of Allergenic Proteins (SDAP) tool and Allergen Online (9).…”
Section: Populus Familymentioning
confidence: 99%